The analysis of woodball game on long-distance shot athletes iwba palembang - M. Taheri Akhbar Taheri (Program Pascasarjana Universitas Negeri Jakarta, 2023)
Abstract The problem of this research is to find out the analysis of the game of woodball in the long-distance shots of Palembang IWbA athletes. The aim of this study was to find out the Long Distance Shots of Palembang IWbA Athletes. The method used is the descriptive qualitative method. The object of research is four athletes, coaches, and the chairman of Palembang woodball. Data collection techniques using observation, interviews, and documentation. The data analysis steps are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the analysis of the ability to hit long distances in Palembang woodball athletes is: 1) Implementation of Palembang IWbA athlete training which is currently not optimal and still has problems in hitting long distances 2) The basic technical skills of long-distance shots have not been achieved 3) Several factors inhibiting the development of woodball in Palembang. 4) The coach's difficulty in training or explaining long-distance shots. Keywords: Woodball Game, Long-Distance Shot